The impact of wearable sports equipment on college students’ physical exercise persistence: a mediated model of physical exercise motivation moderated by social support - Han, Yufeng; Wang, Sen; Zhang, Zhiwen; Fan, Junli (Frontiers in Sports and Active Living, 2025)
BackgroundUnder the strategic framework of “Healthy China,” the issue of insufficient exercise adherence among college students has become increasingly prominent. As an emerging intervention tool, wearable sports equipment (WSE) holds potential in addressing this issue, yet its effectiveness may be influenced by exercise motivation and social support. Existing studies have primarily focused on the independent effects of technological interventions, with limited exploration of the psychosocial mechanisms involved.ObjectiveDrawing upon Self-Determination Theory and Social Support Theory, this study constructs a mediated model of exercise motivation to examine the mechanisms through which WSE influences exercise adherence among college students, with a particular focus on the mediating role of exercise motivation and the moderating effect of social support.MethodsA cross-sectional survey was conducted using stratified cluster sampling among 1,286 students from six universities across China. Core variables were measured using the Perceived Use of Wearable Equipment Scale, Exercise Adherence Scale, Exercise Motivation Scale, and Social Support Scale. Model 59 of the SPSS PROCESS macro was employed for data analysis.ResultsWSE use significantly predicted exercise adherence (β = 0.143, p < 0.001), with exercise motivation partially mediating this relationship (accounting for 27.3% of the total effect). Social support exhibited a dual moderating effect: it strengthened the direct effect of WSE on exercise adherence (β = 0.204 under high support vs. β = 0.082 under low support), but weakened the effect of WSE on exercise motivation (non-significant under high support, β = 0.219 under low support), as well as the indirect effect of WSE on exercise adherence via motivation (β = 0.116 under high support vs. β = 0.463 under low support).ConclusionWSE impacts exercise behavior through the synergistic interplay of exercise motivation and social support. Intervention strategies should be tailored according to individuals’ levels of social support—those with low support should focus on strengthening motivational internalization, while those with high support may benefit more from the direct reinforcement of technological feedback. The findings provide a theoretical basis for optimizing health promotion strategies in higher education institutions.